Special Issue “Adenosine Receptors as Attractive Targets in Human Diseases” - Daniela Catarzi; Flavia Varano; Vittoria Colotta (Pharmaceuticals, 2021)
The idea of promoting this Special Issue arises from the desire to witness the multidisciplinary efforts that are currently in progress to provide new insights into the pathophysiological role of adenosine [...]